Younger patients have an increased risk for dementia after coronary artery bypass grafting, a population-based cohort study from the SWEDEHEART registry. (25th November 2020) - Nielsen, S; Giang, K.W; Karlsson, M; Hansson, E.C; Pivodic, A; Lindgren, M; Jeppsson, A
Abstract: Background: Previous studies investigating the association between coronary artery bypass grafting (CABG) and risk for dementia show conflicting results. Purpose: To compare the long-term risk for dementia in CABG patients to matched individuals in the general population, and to identify independent predictors for developing dementia after CABG. Methods: Data from the SWEDEHEART registry and three other mandatory national registries were merged to compare all patients who underwent isolated CABG in Sweden from 1992 to 2015 (n=111.335) with an age- and sex-matched control individuals from the general population (n=222.396). Cumulative incidence adjusted for the competing risk for death and Cox regression models with Hazard Ratio (HR) and 95% confidence interval (CI) adjusted for age, gender, co-morbidity and socioeconomic variables, were used to calculate the risk of dementia. Median follow-up was 10.1 years (IQR 2.5–14.7) among CABG patients and 10.7 years (5.6–15.7) among the controls. Identified interactions of the excess risk for dementia with sex and age categories (<65, 65-<75, ≥75 years) resulted in analyses being stratified on those sub-cohorts. Results: The overall cumulative incidence at 20 years follow up of all-cause dementia was 9.6% (95% CI 9.4–9.9) among CABG patients and 9.0 (8.8–9.2) among individuals in the general population. The adjusted relative risk for all-cause dementia was increased among CABG patients <65 years and 65–75 years, (HR 1.29 (95% CI 1.17–1.41) and HR 1.06 (1.01–1.11), respectively (fig 1). The risk for all-cause dementia was higher in CABG women than in CABG men (HR 1.62 (1.30–2.03) vs HR 1.22 (1.10–1.35)). In the oldest age group (75 years and older) the risk for all cause dementia, vascular dementia and Alzheimer's disease was lower for CABG patients compared to controls (HR 0.73 (0.69–0.78). Female CABG patients <65 years had an increased risk for Alzheimer's disease (HR 1.83 (1.06–3.15). Hypertension, diabetes, preoperative stroke, renal failure, heart failure, atrial fibrillation, depression and low income were independent predictors for all-cause dementia in CABG patients. Conclusion: CABG patients younger than 75 years at the time of surgery have an increased risk of all-cause dementia compared to an age- and sex-matched population. Women younger than 65 years that underwent CABG had also a markedly higher risk for Alzheimer disease. Increased awareness of the higher risk for dementia in younger CABG patients is warranted to avoid delay of diagnosis and treatment. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): The Swedish Heart and Lung Foundation, Swedish State